Analysis of tar compounds and quantification of naphthalene from thermal treatment of household biowaste. (15th June 2018) - Vakalis, S.; Patuzzi, F.; Moustakas, K.; Sotiropoulos, A.; Malamis, D.; Baratieri, M.
Abstract: Household biowaste represent the organic fraction of municipal solid waste and are an underutilized resource. Although previous studies have performed pyrolysis of organic waste, the vast majority has been on specific presorted feedstock or conventional lignocellulosic streams. Therefore, there is a lack of pyrolysis applications on representative food waste as retrieved from households and this can be attributed primarily to their high water content and their degradability. But via the intermediate step of drying, long-term storage and thermal treatment have become possible. In the framework of this study, household biowaste were pyrolyzed for the production of carbonaceous materials with a main focus on the analysis of produced tar compounds. Tars can be corrosive or cause clogging and disrupt the operation of pyrolysis and gasification plants. Their analysis has faced several difficulties due to inconsistency in the methodologies that have been applied by various groups. The tar protocol has provided a solid framework for consistent analysis of tars but until now has been solely used for the case of gasification. This study aimed to apply the tar protocol for pyrolysis and to enhance the detectability of the method for a wider range of tars by means of elemental analysis, attenuated total reflectance (ATR) and gas chromatography-mass spectrometry (GC-MS). GC- MS was performed by means of a specific column for PAHs identification and calibration methods were developed for the proper quantification of naphthalene which is the dominant tar compound. The results of the analysis showed that naphthalene concentration increased from torrefaction to carbonization but then decreased significantly for high temperature pyrolysis at 860 °C. Highlights: Analysis of tar compounds from pyrolysis of food waste. Representative food waste feedstock that was sampled from households. Application of the tar protocol - technical specification CEN/TS 15439. Enhancement of the tar protocol with ATR and GC-MS analysis. Additional calibration for the accurate quantification of naphthalene.